15. STUDY ON LOWER GENITAL TRACT INFECTIONS IN PREGNANT WOMEN AT ≥ 35 WEEKS OF GESTATION AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and subclinical characteristics and identify common pathogens causing vaginitis in pregnant women at ≥ 35 weeks of gestation at the National Hospital of Obstetrics and Gynecology.Subjects and methods: A cross-sectional descriptive study was conducted on 124 eligible pregnant women. Participants underwent gynecological examinations and vaginal discharge testing (wet mount microscopy and Gram staining using the Nugent scoring system). Data were analyzed using SPSS version 20.0.Results: The prevalence of vaginitis was 30.6%, primarily caused by Candida species (30.6%), while nonspecific vaginitis accounted for 4.8%. No cases of Trichomonas infection were recorded. Common clinical symptoms included abnormal vaginal discharge (52.4%) and vulvar pruritus (5.6%). A significant association was found between a history of vaginitis and current infection (p < 0.05).Conclusion: Vaginitis in pregnant women at ≥ 35 weeks is mainly caused by Candida spp. Timely detection and treatment are essential to reduce the risk of adverse pregnancy outcomes.
Keywords: Vaginitis; pregnant women; Candida; Nugent; vaginal microbiota.